Project SMILE with a HEART: Cultivating Action Researches in the Schools Division Office of Deped Camarines Sur, Philippines - Casyao – Doroin, Josephine (JPAIR Institutional Research, 2020)
Project SMILE with a HEART in Research desires to improve and develop a positive attitude in making and implementing research in SDO Camarines Sur. SMILE, which stands for Share, Mentor, Initiate, Learn, and Excel, were strategies done by the Division Research and Development CI team, with a positive outlook and insights that a researcher should possess HEART- Hardworking, Enthusiastic, Authentic, Resourceful, and Transformational. This study aims to determine the impact of the project in the Action Research (AR) competencies and initiatives of personnel. A descriptive-quantitative method was employed in discussing the responses. Quantitative data were derived from the researcher-made questionnaire. Total enumeration of 18 CI Teams of Class III served as respondents. Analyzed data revealed that before the implementation of the project, the competency level of researchers on the AR process is moderately competent, with strengths and challenges encountered in the AR process. The AR project is fairly difficult. The activities and strategies implemented, such as training, mentoring and coaching, visual management, mistake proofing, and simplified process, were extremely accepted and demonstrated that it was very effective, with 100% approval of researches submitted. Thus, the project implemented improves the research competencies of personnel, and it develops a positive attitude towards research undertakings. This was funded under the Basic Education Research Fund (BERF) through the Division/Region Research Committee and PPRD Region V.
Keywords: research programs and services; action research competencies; continuous improvement; descriptive-quantitative; Philippines